المسؤولية الطبية في الفقه الإسلامي - د. محمد السائح الكوربو (Aljameai, 1970)
الملخص:تتناول هذه الدراسة بالبحث موضوع المسؤولية الطبية وموقف الفقهاء المسلمين في المذاهب الأربعة منها، حيث تعرضت إلى تعريف المسؤولية الطبية ومدى مشروعيتها ، وأنواع المسؤولية الطبية في القانون الوضعي ، ومقارنتها بالفقه الاسلامي ، وطبيعة التزام الطبيب في الفقه الاسلامي ، وهل هو مطالب ببذل عناية أم بتحقيق غاية ، حيث خلصت الدراسة إلى  أنه مطالب ببذل عناية ، تأتي بعدها الغاية المنشودة وهي الشفاء بإذن الله تعالى.وأن الطبيب يعتبر أجيراً مشتركاً ، وبالتالي فإن يدهُ يدُ ضمانٍ على اختلاف بين العلماء . AbstractThis study deals with the topic of medical responsibility and the position of Muslim jurists in the four schools of thought, as it was exposed to the definition of medical responsibility and the extent of its legitimacy, the types of medical liability in positive law and its comparison with Islamic jurisprudence, and the nature of the doctor’s commitment in Islamic jurisprudence, and whether he is required to exert care or to achieve a goal, where The study concluded that he is required to exert care that comes after the desired goal, which is healing, God Almighty willingAnd that the doctor is considered a joint employee, and therefore his hand is a guarantee against the difference between the scholars